AGRICULTURAL CONTROL MECHANISMS PROCEDURE FOR IMPLEMENTATION OVER AUTHORITIES - Raufov , Quvonchbek Khusin ugli (Educational Research in Universal Sciences, 2024)
In this article, the public control mechanism and the new works carried out over local executive bodies, the role of local bodies in the establishment of New Uzbekistan and the women’s register, the iron register, and the youth register are widely discussed.